Analisis Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Harga Terhadap Keputusan Pembelian Pada onsumen Rown Division Kota Surakarta - Utama, Prayusa Widya, Drs. Ma'ruf, M.M (2015)
The purpose of this study was to examine or analyze the effect of product quality, service quality, and price on purchase decisions in rown Divison Surakarta. This research is quantitative. The data used in this research is primary data and data collection methods in this study was a questionnaire method. The population in this study is that consumers rown Division Surakarta. The sample of 100 taken at random. The sampling technique in this study using a convenience sampling method. Data analysis methods used include quality test data collection (validity, reliability), classical assumption (normality test, multicollinearity, heteroscedasticity test), and hypothesis testing (multiple linear regression, t-test, F and coefficient of determination). Based on the test results and analysis, variable product quality, service quality, and the price significantly influence purchase decisions on rown Division Surakarta. This shows that the absence of quality products, services, and high and low prices affect the purchase decision. Keywords: Quality Products, Quality Service, Price